Dative Shift in Croatian - Zovko, Irena (2000)
Many syntactic theories see dative shift as a construction that results in the change of grammatical relations within the sentence, whereas Role and Reference Grammar sees it as variable linking to the semantic macrorole of undergoer in the syntax-to-semantics linking algorithm. Croatian is a case-marking language in which the equivalent of any two English sentences containing a verb that allows dative shift would always be a single Croatian sentence, as in (1): (1) a. Sloan gave the photo to Tom. b. Sloan gave Tom the photo. c. Sloan je Tom-u da-l-a Sloan AUX-3sg Tom-DAT.sg.MASC give-PAST-3sg.FEM fotografij-u. photo- ACC.sg.FEM However, there are two verbs in Croatian (with their aspectual pairs) that allow variable linking to undergoer: darivati / darovati ( to give as gift ), and nuditi / ponuditi ( to offer ). These verbs may also be considered to allow dative shift if we take into account the fact that the traditional indirect object in the dative can become the direct object in the accusative, resulting in a slight change of meaning (2): (2) a. Samostan-0 je bolnic-i Convent-NOM.sg.MASC AUX.3sg hospital-DAT.sg.FEM darova-o hran-u. give.as.gift-PAST.sg.MASC food-ACC.sg.FEM b. Samostan-0 je bolnic-u convent-NOM.sg.MASC AUX.3sg hospital-ACC.sg.FEM darova-o hran-om. give.as.gift-PAST.sg.MASC food-INST.sg.FEM By analyzing a number of Croatian examples involving these two verbs, we shall try to shed some light on the fact that their use in the dative shifted form is not very frequent, that it is limited to particular contexts of situation (thus being restricted to specific semantic domains), and that it depends on the semantic characteristics of the Patient/Theme element.